Firm-level estimates of fuel substitution: An application to carbon pricing - Marie Hyland; Stefanie Haller (University College Dublin, UCD School of Economics, 2015)
We estimate partial- and total-fuel substitution elasticities between electricity, gas and oil, using firm-level data. We find that, based on the partial elasticity measure, electricity is the least-responsive fuel to changes in its own price and in the price of other fuels. The total elasticity measure, which adjusts the partial elasticity for changes in aggregate energy demand induced by individual fuel price changes, reveals that the demand for electricity is much more price responsive than the partial elasticity suggests. Our results illustrate the importance of accounting for the feedback effect between interfactor and interfuel substitution elasticities when considering the effectiveness of environmental taxation. We use the estimated elasticities to simulate the impact of a e15/tCO2 carbon tax on average energy- related CO2 emissions. The carbon tax results in a small reduction in CO2 emissions from oil and gas use, but this reduction is partially offset by an increase in emissions due to increased electricity consumption by some firms.
Keywords: D24; Q38; Q41; Q48; Q58; 330; fuel substitution; firm-level data; environmental taxation